Strategi Pengembangan Usaha Kelompok Tani Mekar di Kelurahan Lapangan, Kecamatan Mapanget, Kota Manado - Pasolang, Puja; Waney, Nordy Fitsgeral Lucky; Lumingkewas, Jelly Ribka Danaly (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2025)
This study aims to analyze business development strategies in the Mekar farmer group in Lapangam Village, Mapanget District, Manado City. This research was conducted from June to August 2024. Data collection using the survey method. The data sources used were primary data and secondary data. Primary data was obtained through two stages, namely Focus Group Discussions (FGDs) conducted with stakeholders, namely government agencies of the Agriculture Office, Food Service, and heads of farmer groups to identify indicators of internal and external factors. The second stage is an interview conducted using a questionnaire to 13 farmer group members. Secondary data was obtained from literature studies in the form of books, journals and theses. The sample used in this study was taken by purposive sampling method. The results showed that the business development strategy of the Mekar Farmer Group, namely, (1) Skilled and experienced human resources can be used to build distribution networks, maximizing the benefits of strategic location and market access. (2) Using large and fertile land and agricultural equipment to produce products in large quantities and offer lower prices, so as to meet the high market demand and increase competitiveness. (3) Leverage the support of government agencies for training and skills development programs for human resources. (4) Utilize agricultural technology to maximize the use of equipment and land, thereby increasing production and lowering operational costs.